David Henn, C. J. Cela: "La colmena". Grant & Cutler-Tamesis Books, London, 1974; 80 pp. (Critical Guides to Spanish Texts, 11). - Aveleyra-Sadowska, Teresa (El Colegio de México, 1976)
Se reseñó el libro: C. J. Cela: "La colmena".